Planung, Durchführung und Evaluation der Lehrveranstaltung "Digitale Grundbildung" (Pedagogical Horizons, 2021)
This paper explains and describes the implementation of a course ("Digital Basic Education") in Educational Sciences at the Private University of Education of the Diocese of Linz (PHDL) in the form of a hybrid seminar setting. The article provides an inventory based on the planning of the methodological-didactic settings to be applied up to an evaluation including and reflecting on scientific models such as the "ADDIE" model.The presented teaching-learning scenarios in hybrid learning settings provide a basis, foundation and suggestions for students of the course "Digital Basic Education" in the Master's programme for secondary school teachers at the PHDL to develop their own digital self-learning scenarios, to transfer and use them in everyday pedagogical practice in the sense of action-oriented media education (Schorb, 2017, p. 134ff.).